RF and microwave high‐Q floating active inductor design and implementation. (3rd April 2014) - Branchi, P.; Pantoli, L.; Stornelli, V.; Leuzzi, G.
Summary In this paper, a high‐Q floating active inductor (FAI), suitable for RF and microwave applications, is presented. The proposed FAI is based on two cascaded pairs of highly linear capacitance gyrators, which provide a symmetric and reciprocal structure. The proposed FAI shows fully symmetrical two‐port characteristics, high quality factor and high linearity. As a feasibility demonstration, a prototype of the designed FAI has been fabricated, together with an LC series band‐pass filter. At the operating frequency, the real part of the impedance of the equivalent FAI is very low (Req = 0.0039 Ω), providing a very high quality factor. The filter has a central frequency of 430 MHz and a −3 dB bandwidth of about 9 MHz. Copyright © 2014 John Wiley & Sons, Ltd.